Robinia pseudoacacia decline and fine root dynamics in a plantation chronosequence in the Yellow River Delta, China - Longmei Guo; Yuanxiang Pang; Banghua Cao; Zhaofei Fan; Peili Mao; Zexiu Li; Wei Liu; Pengfei Li (Forest Science, 2022)
Fine roots (<2 mm in diameter) play a significant role in tree growth and stand productivity. However, knowledge of fine root dynamics in saline alkali soil remains limited. Using sequential soil core and ingrowth core methods, we assessed the dynamics of aboveground biomass (AGB) and production (AGP), fine root biomass (FRB), production (FRP) and turnover (FRT), and soil properties (water content [SWC], salt content [SSC], pH and nutrients) in 2-, 18-, 32- and 42-year-old black locust (Robinia pseudoacacia L.) stands in the Yellow River Delta, China. Corresponding to the unimodal growth pattern in AGP, the AGB of black locust rapidly increased until age 32 and then slowed down. In contrast, across all depths, FRB and FRP took a unimodal pattern with a decrease in growth around age 32, and FRT continually decreased with stand age. SWC and soil nutrients increased with stand age, whereas SSC and pH decreased with stand age until age 32 and then increased. Based on the correlation analysis, we may presume that in addition to the age effect, the decline of black locust in AGP is most likely caused by SWC, SSC, and pH stresses through the dysfunction in nutrient absorption by fine roots.